(untitled) (Journal of Bangladesh Academy of Sciences, 2023)
The genus Wendlandia includes around 70 species and is native to southeast Asia, northeast Africa, China, Australia, and Turkey. Mnay plant species of this genus have ethnomedicinal properties, which are used to deal various health complications, including dysentery, severe fever, cough, diabetes, hypertension, hyperlipidemia, constipation, and inflammation. This review sought to summarize details on the ethnomedicinal uses, phytochemical composition, safety aspects, and toxicology of Wendlandia species. Additionally, it covered the nomenclature, distribution, taxonomy, and botanical characteristics of this genus. Several electronic databases were used to retrieve the information, including Google Scholar, PubMed, Web of Science, Scopus, Science Direct, and Springer Link. The Plant List (www.theplantlist.org) was used for taxonomical authentications. SciFinder and PubChem were utilized for the verification of chemical structures and IUPAC (International Union of Pure and Applied Chemistry) name of the compounds. Numerous examinations of chemical constituents of the Wendlandia genus have identified approximately 60 essential plant compounds, such as iridoid glycosides, flavonoids, flavonoid glycosides, carotenoids, and triterpenes. Various research studies have showcased the therapeutic potential of Wendlandia species, highlighting their abilities in treating diabetes, combating oxidation, reducing inflammation, fighting microbes, lowering blood pressure, and potentially hindering cancer growth. The significance of Wendlandia in traditional medicine systems and its role as a valuable origin of impactful natural compounds are evident. This review provided scientific basis for future endeavors, including chemical investigations into already studied species and other less studied species of Wendlandia for finding future lead compounds. J. Bangladesh Acad. Sci. 47(2); 139-154: December 2023